Self‐healable, recyclable, ultrastretchable, and high‐performance NO2 sensors based on an organohydrogel for room and sub‐zero temperature and wireless operation. Issue 1 (29th July 2022) - Ding, Qiongling; Zhou, Zijing; Wang, Hao; Wu, Zixuan; Tao, Kai; Yang, Bo‐Ru; Xie, Xi; Fu, Jun; Wu, Jin
Abstract: To date, development of high‐performance, stretchable gas sensors operating at and below room temperature (RT) remains a challenge in terms of traditional sensing materials. Herein, we report on a high‐performance NO2 gas sensor based on a self‐healable, recyclable, ultrastretchable, and stable polyvinyl alcohol–cellulose nanofibril double‐network organohydrogel, which features ultrahigh sensitivity (372%/ppm), low limit of detection (2.23 ppb), relatively fast response and recovery time (41/144 s for 250 ppb NO2 ), good selectivity against interfering gases (NH3, CO2, ethanol, and acetone), excellent reversibility, repeatability, and long‐term stability at RT or even at −20°C. In particular, this sensor shows outstanding stability against large deformations and mechanical damages so that it works normally after rapid self‐healing or remolding after undergoing mechanical damage without significant performance degradation, which has major advantages compared to state‐of‐the‐art gas sensors. The high NO2 sensitivity and selectivity are attributed to the selective redox reactions at the three‐phase interface of gas, gel, and electrode, which is even boosted by applying tensile strain. With a specific electrical circuit design, a wireless NO2 alarm system based on this sensor is created to enable continuous, real‐time, and wireless NO2 detection to avoid the risk of exposure to NO2 higher than threshold concentrations. Abstract : For the first time, a self‐healing, recyclable, and degradable NO2 gas sensor is reported based on an ultrastretchable and stable polyvinyl alcohol–cellulose nanofibril double‐network organohydrogel, which is synthesized using a facile one‐step polymerization method based on glycerol‐induced formation of hydrogen bonds. The NO2 sensor features ultrahigh sensitivity (372%/ppm), low limit of detection (2.23 ppb), excellent selectivity, repeatability, and full reversibility at and below room temperature, enabling the real‐time, wireless, and continuous monitoring of trace NO2 based on a designed wireless alarm system.